Dynamics of the O. felineus Infestation Intensity and Egg Production in Carcinogenesis and Partial Hepatectomy in the Setting of Superinvasive Opisthorchiasis - Vitaly G. Bychkov; Ludmila F. Kalyonova; Elena D. Khadieva; Semen D. Lazarev; Ilgiz R. Lukmanov; Vladimir A. Shidin; Evgeny N. Morozov (Analytical Cellular Pathology)
Clinical and experimental studies have shown that opisthorchii tend to evade tumour growth foci to colonize more distant areas of the liver. When modelling tumours with various carcinogens in the setting of superinvasive opisthorchiasis, the intensity of invasion is reduced both before the formation of neoplasms (>120 days) and after the development of tumours of various histogeneses (liver, pancreas, and stomach) (>240 days). Egg production was observed to increase with the decrease in the number of parasites in the liver. The smallest changes in the infestation intensity indicators and egg production were observed in the experimental stomach tumours (p>0.05). A partial hepatectomy in the setting of opisthorchiasis did not affect the number of parasites in the ecological niche (liver) or the production of eggs by the helminth. With the deterioration of the vegetation state, parasite clumps of opisthorchii increase egg production under the conditions of distress.